The impact of financial shocks on the forecast distribution of output and inflation - Mario Forni; Luca Gambetti; Nicolò Maffei-Faccioli; Luca Sala (Norges Bank, 2023)
Financial shocks represent a major driver of fluctuations in tail risk, defined as the 5th percentile of the forecast distributions of output and inflation. Since the variance and the asymmetry of the forecast distributions are largely driven by the left tail, financial shocks turn out to play a prominent role for distribution dynamics. Monetary policy shocks also play a role in shaping risk, although its effects are smaller than those of financial shocks. These findings are obtained using a novel econometric approach which combines quantile regressions and Structural VARs.
hdl:11250/3058242
Keywords: C32; E32; 330; Tail Risk; Uncertainty; Skewness; Forecast Distribution; SVAR; Financial shocks; Monetary Policy Shocks; Quantile Regressions